Tailoring Managers’ Journeys Through the AI Transformation of SMEs - Vanja Bevanda (Engineering Proceedings)
Navigation through AI transformative initiatives is challenging for small and medium enterprises (SMEs) in the Mobility–Transport–Automotive (MTA) ecosystem. To move to a higher AI maturity level, they should work on the improvement of indicators in several dimensions. The main role in these processes is assigned to the SME’s manager, but contemporary research is the least concerned with their support. This paper aims to shed light on supporting the strategic decisions that facilitate SMEs’ implementation of AI services (AIaaS). Applying the principles of design thinking to the design of AI services, the author describes the role of SME managers in AI transformation processes as a base for future AIaaS design.